Prove that:

x - tan^-1(x) = tan^-1{(tanx - x)/(xtanx + 1)}

plz help

2 answers

recall that

tan(A-B) = (tanA-tanB)/(1+tanAtanB)
41
Similar Questions
  1. Did I do this problem right?Find the first and second derative-simplify your answer. y=xtanx y'= (x)(sec^2 x)+(tanx)(1) y'=
    1. answers icon 1 answer
  2. Prove cotx-1/cotx+1 = sec2x - tan2xI prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx
    1. answers icon 1 answer
  3. Perform the addition or subtraction.tanx - sec^2x/tanx tan^2(x)/tan(x) - sec^2x/tanx = tan^2x sec^2x / tanx then I use the
    1. answers icon 1 answer
  4. How do I prove that7sin^2x - sinxcosx = 6 can also be written as tan^2x + tanx - 6 = 0 ?
    1. answers icon 2 answers
more similar questions